THE AGENCY FOR FUNDAMENTAL RIGHTS AND ITS ROLE WITHIN THE FRAMEWORK OF THE EUROPEAN UNION - Isabela, STANCEA; Raluca, GHERGHINA (Strategii Manageriale, 2014)
The European Union's agency for Fundamental Rights represents one of the Union's decentralized agencies, established to provide expert advice to the European institutions and essentially aims to ensure that the fundamental rights of the people living in the European Union are protected. Thus fundamental rights are established through minimum standards to ensure that every citizen is treated with dignity. Starting with the right to be free, the right not to be discriminated on grounds of age, disability or ethnic origin, the right to protection of personal data or the right to free access to justice and many other rights should be promoted and protected.